From Catharine Beecher to Martha Stewart : a cultural history of domestic advice - Leavitt, Sarah Abigail (University of North Carolina Press, 2002)
This study demonstrates that today's domestic advice writers -women such as Martha Stewart, Cheryl Mendelson and B. Smith - are part of a long tradition. Sarah A. Leavitt crafts a cultural history and genealogy of domestic advice, based on her readings of manuals spanning 150 years of history.